Male lineages in Brazilian populations and performance of haplogroup prediction tools - Jannuzzi, Juliana; Ribeiro, Julyana; Alho, Clarice; de Oliveira Lázaro e Arão, Grasielly; Cicarelli, Regina [UNESP]; Simões Dutra Corrêa, Heitor; Ferreira, Suelen; Fridman, Cíntia; Gomes, Verónica; Loiola, Silvia; da Mota, Mariana Flavia; Ribeiro-dos-Santos, Ândrea; et al. (Elsevier, 2020)
The use of Y-chromosomal genetic markers in forensic investigations demands the establishment of reliable and representative DNA databases of different reference populations. The genetic characterization of the Y chromosome variation in human populations requires the analyses of haplotype frequencies allied to haplogroup determination. The present study aimed to contribute to the Brazilian database by providing 1,382 Yfiler Plus individual profiles, from 11 Brazilian states. The Yfiler Plus markers showed high haplotype diversities in all Brazilian populations (>0.9970), allowing high intra-population discrimination in forensic investigations. Pairwise genetic distances showed a homogeneity between Brazilian populations (FST ≤ 0.0043; non-differentiation p-values ≥ 0.0212), indicating that admixed populations from Brazil can be represented in a single Yfiler Plus haplotype database, for forensic purposes. The performance of Haplogroup Predictor and NevGen software in haplogroup prediction based on Yfiler Plus and Yfiler haplotypes was evaluated in a subset of 416 Brazilian samples that were also genotyped for 51 Y-SNPs. In 25% of the samples, no classification or errors were found for at least one of the prediction tools or marker sets. NevGen presented lower error rates (5.52% and 8.65% with Yfiler Plus and Yfiler, respectively) than Haplogroup Predictor (16.11% with Yfiler Plus and 13.70% with Yfiler). In conclusion, both haplogroup prediction tools can be useful to direct the SNP typing, but present large error rates to be used in forensic analysis, especially in predicting African haplogroups in admixed South American populations.
Keywords: Admixed populations; Haplogroup prediction; Y-STRs; Yfiler Plus kit